2018
DOI: 10.4025/actascitechnol.v40i1.35460
|View full text |Cite
|
Sign up to set email alerts
|

<b>Integration of Nile tilapia (<i>Oreochromis niloticus </i> L.) production <i>Origanum majorana</i> L. and <i>Ocimum basilicum </i> L. using aquaponics technology

Abstract: This study aims to evaluate the effect of different initial densities of Nile tilapia fingerlings on water quality, fish growth, and production of marjoram (Origanum majorana L.) and sweet basil (Ocimum basilicum L.) in a recirculating aquaponic set up. The experiment was carried out on randomized block design and comprised four fish densities (0, 150, 250 and 500 fish m-3) and two crops, in which each treatment was continued for 45 days and replicated three times. Except for pH and total alkalinity, all water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Basil produces 1.8 kg per meter square under aquaponic production, and only 0.6 kg per meter square in soil cultivation [19]. Thus, aquaponic production is considered to be more efficient and environmentally friendly than soil cultivation [20]. Basil is among one of the top priorities for farmers all over the world due to the high value that it carries as a cash crop [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Basil produces 1.8 kg per meter square under aquaponic production, and only 0.6 kg per meter square in soil cultivation [19]. Thus, aquaponic production is considered to be more efficient and environmentally friendly than soil cultivation [20]. Basil is among one of the top priorities for farmers all over the world due to the high value that it carries as a cash crop [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…-evaluation of different systems (Rocha et al, 2017;Pinho et al, 2021a), system scales (David et al, 2022), combinations of vegetable and fish species (Pinho et al, 2015;2017;2018;Lima et al, 2021), and vegetable and shrimp species (Pinheiro et al, 2017;2020;Lima et al, 2019;Shardong et al, 2020); -comparison of 'traditional' and 'alternative' fish species (Pinho et al, 2021c) and multitrophic systems with shrimp and tilapia cultures (Poli et al, 2019); -influence of parameters such as hydroponic solution concentrations (Sterzelecki et al, 2021), fish densities (Hundley et al 2018), nutrient supplementation techniques (Doncato and Costa, 2021), irrigation regimes (Silva et al, 2022), salinity (Lenz et al, 2017) and levels of crude protein in fish diets (Pinho et al, 2021d) on system performance; -strategies for preventing mineral deficiency in plants (Cerozi, 2020); -adoption of aquaponics for familiar food production in urban (Colucci and Sganzetta, 2021) and rural areas (Silva and Van Passel, 2020), including assessment of drivers and barriers (Brewer et al, 2021); -remote monitoring of water quality (Valero et al, 2020). Most studies do not address waste streams that stem from aquaponic systems.…”
Section: Review Of Brazilian Productionmentioning
confidence: 99%
“…It is important to keep in mind that when handling different crop cycles, a single planting of aquaculture species can represent a different number of plant harvests. [51] reported that for basil crops, 3 harvests were generated throughout the tilapia cycle.…”
Section: Yield and Water Usementioning
confidence: 99%